The Independence of Central America and the Foreign Influence - Puente-Martín, Carlos (2021)
The main target of the article is to understand the evolution of the independence process of the colonies of the Spanish Empire in Central America. It is suggested not only the influence of liberal ideas from Europe after the French Revolution of 1789 but also the example of the independence of the United States. The independence process in Central America was a peaceful movement in contrast to the military confrontations with the royalist troops of the Spanish Monarchy elsewhere. The importance of the participation of the military and politicians in the struggle for independence is underlined, but the participation of the most basic religious establishment, the priests, was of great importance. The legal texts of the Independence Acts of 1821 and 1823 and the Act of the Annexation of Central America to the Mexican Empire are used to assess the role played by the popular will during the independence process against the influence of other foreign States. A reflection on the influence of the United States foreign policy and, especially, of the Monroe Doctrine marks the difference between independence and sovereignty in the independence process of the Central American provinces. The geopolitical importance of the region attracted the interest not only of the European powers, especially Great Britain, but also the United States during the period covered by this article. The political, economic, and social instability that followed the independence process was used by the North American giant to open a waterway that would allow the communication between the Atlantic and Pacific coasts, contributing to the expansion of a new kind of imperialism